Blueberry bagasse recovery for the development of enriched juices - Molina, Adriana K. (2022)
The blueberry, Vaccinium corymbosum L., is considered one of the most antioxidant fruits and it is consumed worldwide for its properties [1]. The development of different industrialized products, as juices and derivatives, generates a considerable quantity of residues, such as bagasse, which are rarely used by the industry for other applications [2]. However, these residues contain valuable chemical compounds that can provide beneficial properties to human health [3]. The main interest of this study was, therefore, to recover the bagasse produced in blueberry juice production to prepare a rich extract to incorporated in the juice. Thus, juices with and without bagasse extract were developed, analyzed, and compared in order to validate the applicability of the extract in this matrix, to enhance the bioactive properties (antioxidant and antimicrobial), the nutritional value (AOAC methods), and the composition in free sugars (HPLC-RI) and phenolic compounds (HPLC-DAD/ESI-MS). The two juices presented a balanced nutritional value, with carbohydrates as the main macronutrients. The free sugars found in higher concentrations were fructose and glucose. In terms of phenolic composition, in the juice and extract-enriched juice, the same nonanthocyanin compound was detected (3-O-caffeoylquinic acid). Regarding anthocyanins, both samples revealed cyanidin derivatives as main compounds. Regarding bioactive properties, the juice enriched with the bagasse extract showed higher antioxidant capacity than the blueberry juice. None of the two juices showed cytotoxicity, being considered safe for consumption. Thus, this study corroborated the importance of the recovery of food industry waste for the development of novel foodstuff.